Effect of Zilgrei Method and Lumbal Massage Combination on Labor Progress During Latent Phase of First Stage of Labor in Primigravida - Melati Yuliandari; Leri Septiani; Roni Rowawi; Sri Komalaningsih; Herry Garna (Universitas Islam Bandung, 2020)
The first stage of labor starts from the onset of cervical dilatation and divided into latent and active phases. The latent phase is a more prolonged phase of labor, which allows various interventions performed. Interventions and the latent phase's length may lead to anxiety and restlessness, which might contribute to prolonged labor when experienced by women in labor. A combination of the Zilgrei method and lumbar massage used to reduce labor pain. This method combines movement, change of position, breathing exercise, and the light massage performed since the first stage of labor. It expected that the work of interrelated pelvic muscles becomes harmonized; hence, the cervix will be softer, and the uterine muscles may push the fetus towards the birth canal. This study aimed to determine the effect of the Zilgrei method and lumbar massage combination on the latent phase of the first stage of labor progress in primigravida. It is a quantitative quasi-experimental study on 66 women who underwent the latent phase of the first stage of labor in independent practice of midwife the work area of Citarip Public Health Center during May–July 2019, who were divided equally into control and intervention groups. The statistical analysis used was univariate and bivariate analyses with an independent t test. The mean duration of labor in the latent phase of the first stage of labor in the control group and intervention group was 368 minutes and 307 minutes, respectively, with a difference of 61 minutes (p=0.002). Therefore, the Zilgrei method and lumbar massage combination significantly affect labor progress in the latent phase of the first stage of labor in primigravida. PENGARUH KOMBINASI METODE ZILGREI DAN PEMIJATAN LUMBAL TERHADAP PROSES KEMAJUAN PERSALINAN PADA PRIMIGRAVIDAKala I persalinan merupakan tahap serviks terbuka yang terdiri atas fase laten dan fase aktif. Fase laten mempunyai durasi persalinan lebih panjang sehingga memungkinkan banyak intervensi. Intervensi dan lama fase laten dapat menimbulkan kecemasan dan kegelisahan, apabila dialami ibu in partu dapat menjadi faktor persalinan lama. Kombinasi Metode Zilgrei dan pemijatan lumbal menjadi metode mengurangi rasa nyeri persalinan yang menggabungkan gerakan, perubahan posisi, latihan pernapasan, dan pijatan ringan yang dipersiapkan sejak kala I persalinan. Diharapkan kerja otot panggul saling berkaitan menjadi selaras sehingga serviks tidak kaku dan terdapat potensi otot rahim mendorong janin menuju jalan lahir. Tujuan penelitian ini mengetahui pengaruh kombinasi Metode Zilgrei dan pemijatan lumbal terhadap kemajuan proses persalinan kala I fase laten pada primigravida. Penelitian ini merupakan penelitian kuasi eksperimental kuantitatif pada 66 wanita yang menjalani fase laten persalinan kala I di bidan praktik mandiri (BPM) wilayah kerja Puskesmas Citarip periode Mei–Juli 2019 yang dibagi rata menjadi kelompok kontrol dan intervensi. Analisis statistik menggunakan analisis univariat dan bivariat dengan uji t independen. Durasi persalinan kala I fase laten rerata kelompok kontrol dan intervensi adalah 368 menit dan 307 menit masing-masing dengan selisih waktu 61 menit (p=0.002). Simpulan. kombinasi Metode Zilgrei dan pemijatan lumbal berpengaruh terhadap kemajuan proses persalinan kala I fase laten pada primigravida.